Exposure to Antibiotics and Neurodevelopmental Disorders: Could Probiotics Modulate the Gut-Brain Axis? - Tamara Diamanti; Roberta Prete; Natalia Battista; Aldo Corsetti; Antonella De Jaco (MDPI AG, 2022)
In order to develop properly, the brain requires the intricate interconnection of genetic factors and pre-and postnatal environmental events. The gut-brain axis has recently raised considerable interest for its involvement in regulating the development and functioning of the brain. Consequently, alterations in the gut microbiota composition, due to antibiotic administration, could favor the onset of neurodevelopmental disorders. Literature data suggest that the modulation of gut microbiota is often altered in individuals affected by neurodevelopmental disorders. It has been shown in animal studies that metabolites released by an imbalanced gut-brain axis, leads to alterations in brain function and deficits in social behavior. Here, we report the potential effects of antibiotic administration, before and after birth, in relation to the risk of developing neurodevelopmental disorders. We also review the potential role of probiotics in treating gastrointestinal disorders associated with gut dysbiosis after antibiotic administration, and their possible effect in ameliorating neurodevelopmental disorder symptoms.